Effect of low-level laser therapy on stability during retention phase after orhodontic treatment: a randomized controlled trial - Yanpei, Wang (2025)
Low-level laser, also known as weak laser and low-intensity laser normally produce stimulating or positive effects on alveolar bone remodeling, inducing an increase osteoblasts and osteoclast resulting increased the incidence of orthodontic tooth movement (OTM) and inhibitory effects depending on the dose. The aim of this study is to investigate the stability in maxillary dentition after application of low-level laser therapy (LLLT) during leveling and alignment stage of fixed appliances. In this experiment, 20 eligible participants were selected from the random sampling samples of the previous experiments, and the Little's Irregularity Index (LII), intermolar width (IMW), intercanine width (ICW), arch length (AL), overbite(OB), and overjet(OJ) of the maxillary dentition were measured according to the ratio of the laser group: control group = 1;1. The results of the measurements were analyzed by SPSS version 26. Friedman's test and repeated-measures ANOVA were used for statistical comparison. The results of LII, ICW, OB, and OJ were not significant (P > 0.05). However, IMW (P = 0.038) and AL (P = 0.019) was statistically significant. Although the overall effects of LII, ICW, OB and OJ were not significant, the mean values in the laser group were generally smaller compared to control group. LLLT has no significant effects on LII, ICW, OB, and OJ. It was concluded that LLLT only had a subsequent effect on IMW and AL during 12 months of retention period. However, within group changes, LLLT has smaller mean values which indicate the stability over time in the laser group was clearly better than control group to prevent relapse.